2018
DOI: 10.1021/acs.jpcc.8b04209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metal-Optical Properties on Surface-Enhanced Infrared Absorption

Abstract: Surface-enhanced infrared absorption (SEIRA) spectroscopy using resonant metallic nanostructures is increasingly attracting interest during the last decade. Nevertheless, the impact of the metals' intrinsic properties on SEIRA is still little studied. We present an experimental work on this topic, examining the infrared-optical resonance spectra of linear nanoantennas made of five of the most common metals (gold, silver, copper, aluminum, and iron) with respect to the intrinsic and radiation damping. Highly ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Under this assumption, we found that the characteristic enhancement factor of the resonant nanorod antennas (sample B) reads EFeff ≅ 55000. We stress that this figure is competitive with the efficiency of lithographic nanoantenna arrays, [ 62,63 ] even though EFeff is here underestimated.…”
Section: Resultsmentioning
confidence: 97%
“…Under this assumption, we found that the characteristic enhancement factor of the resonant nanorod antennas (sample B) reads EFeff ≅ 55000. We stress that this figure is competitive with the efficiency of lithographic nanoantenna arrays, [ 62,63 ] even though EFeff is here underestimated.…”
Section: Resultsmentioning
confidence: 97%
“…This maximum enhancement is the highest possible if the absorption cross section of the plasmonic structure is equal to the cross section for radiation scattering . Such a situation can be reached with geometrically optimized structures and low electronic damping (perfect crystallinity) of the metal, as shown by measurements and simulations for linear nanoantennas (Figure ). Then, in SEIRA based on IR extinction measurements, extraordinarily enhanced vibrational signals show up, because the vibrational absorption strongly modulates the IR light scattering of the plasmonic system …”
Section: Related Techniquesmentioning
confidence: 93%
“…Bigger enhancement with Cu, Ag, and Au antennas is attained because of the lower electronic damping. Reproduced from ref . Copyright 2018 American Chemical Society.…”
Section: Related Techniquesmentioning
confidence: 99%
“…Each of them is dominated by a broad peak at mid-infrared (MIR) wavelengths, the distinctive evidence of MIR plasmonic resonances. 47,48 With the increasing average AgA particle size, there is also a characteristic gradual red shift of the resonance frequency, in accordance with the theoretical expectations. 49 Note that the resonances with the highest quality factors can be observed on the samples with intermediate growth times (samples b−d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%